Cuticular microstructure of the guard hair in vats from the coastal desert of southern Peru - Medina, Yasmy Karina (2021)
The present study aimed to describe the cuticular microstructure of the guard hairs of bats present in the coastal desert of southern Peru. Samples of 45 bat specimens (16 species, 13 genera and 4 families) from the department of Arequipa were examined, which were part of the scientific collection of mammals of the Natural History Museum of the National University of San Agustín de Arequipa (MUSA). Hairs were obtained from the inter-scapular area, which were observed in a Scanning Electron Microscope to obtain morphological and morphometric data. Five types of coronal cuticular patterns (appressed, divergent, divaricated, alternate and unequal hastate) and six configurations of the edge of the scales (simple, cleft, emarginate, serrated, denticulate and dentate) were recorded, allowing the specimens to be differentiated down to the level of subfamily, while with the help of quantitative data (length and width of hair, Scale Index and Scale Width Index) it was possible to reach a determination down to the species level. For the first time, a description of the guard hair cuticle is documented for 15 species of bats that inhabit the coastal desert of southern Peru. A taxonomic key is presented that will support the development of inventories and monitoring and conservation programmes of bats on the southern coasts of Peru.